’’They are just stuck in that cage which the school is’’ : experience of experts and individuals with mathematical difficulties - Halla Margrét Sigurðardóttir 1994- (2020)
Children and young adults that struggles with learning difficulties often find their 10 years of compulsory education extremely difficult. However, there seems to be a lack of information on adults who struggle with mathematical difficulties. The aim of the study was to gain a better understanding of the difficulties related to mathematics among university students with a qualitative research method. It is believed that a similar study has not been made before among university students in Iceland. Open interviews were conducted with interviewees from the 10th of September 2019 to 23rd of November 2020. Interviewees of the study were university students who reported their experience of difficulties with mathematics and individuals with specialization in learning difficulties. The main findings were that there is a great shortage of research on mathematical difficulties. Both the university students and the specialists generally reported that there was a lack of knowledge and resources for individuals with such difficulties when reaching higher level education. The interviewee’s experience was that discomfort accompanies such learning difficulties and that it is necessary for the students to have been in a supportive and constructive environment through their schooling. It is clear that more emphasis needs to be placed on research in this area, as there is a large increase in the numbers of students in universities. Keyterms: Mathematical difficulties, personal experience, university students, experts, university interventions. Börn og ungmenni sem glíma við námserfiðleika geta upplifað skyldunám sitt afar erfitt. Skortur virðist vera á upplýsingum um fullorðna sem glíma við stærðfræðiörðugleika. Markmið rannsóknarinnar var að fá betri skilning á erfiðleikum tengdum stærðfræði á meðal háskólanema með eigidlegri rannsóknaraðferð, en talið er að sambærileg rannsókn hafi ekki verið gerð áður meðal háskólanema á Íslandi. Tekin voru opin viðtöl við fimm háskólanema og tvo sérfræðinga á haustmisseri 2020. Viðmælendur ...